Mobility from the Catholic Religion to the “without Religion” Identification in Young University Students in Chile (2024)
In recent years, Chile has experienced a highly significant abandonment of the Catholic church. This can be observed in young people, who have left its organizational spaces and their identification with it. The magnitude of this growing abandonment, which has been heighted by the public awareness of sexual abuse committed by priests, has been shown in quantitative studies, however, they do not delve into the reasons of those who distance themselves from the church. This article presents research results that identify the motivations expressed by young people that led them to stop being Catholic and places this phenomenon of disaffection within a bigger issue that has been occurring for some time: that of a religious mobility in an increasingly secular society, where the number of people who identify themselves as “without religion” continues to grow. By means of individual interviews, the reasons given by young people were identified and later validated in a subsequent group interview process.